Psychometric evaluation of the Malay version of the Individual Community-Related Empowerment scale among older adults in Malaysia - Zuraidah Zaidun; Rosnah Sutan; Azimatun Noor Aizuddin (Belitung Raya Foundation, Indonesia, 2023)
Background: Malaysia is projected to become an aged country by 2030, with the older age group comprising 10 percent of the total population. To address this demographic shift, comprehensive plans and initiatives are being implemented at various levels, ranging from the government to local communities. A crucial aspect of these efforts is community empowerment, which requires a reliable and validated tool for measurement. Objective: This study aimed to validate the Individual Community Related Empowerment (ICRE) scale in alignment with the national language of Malaysia. Methods: This cross-sectional study was conducted from May to December 2019. Back-to-back translation from the English to Malay version of the ICRE scale was done. A total of 328 older persons aged 60 years old and above who attended clinics and understood Malay had been randomly selected. Exploratory factor analysis (EFA), particularly Principal Component Analysis (PCA) with Varimax rotation and Kaiser Normalization, was performed in this study using IBM SPSS version 27 Amos graphic. Results: The findings revealed that the Malay version of the Individual Community Related Empowerment (ICRE-m) scale consists of five components: self-efficacy, intention, participation, motivation, and critical awareness, which collectively accounted for 92.3% of total variance. All five components demonstrated Cronbach’s alpha values greater than 0.7, indicating the reliability of the selected items for field studies. Conclusion: The ICRE-m scale is acceptable for field studies and valid for measuring individual-related community empowerment. Nurses and other healthcare professionals can employ this scale specifically within the Malay-speaking population, particularly in the Asian region. Future studies on community empowerment among older individuals can utilize this tool to assess community readiness for participating in community health interventions.